Epidemiological Investigation and Antimicrobial Resistance Profiles of Salmonella Isolated From Breeder Chicken Hatcheries in Henan, China - Xu, Yaohui; Zhou, Xiao; Jiang, Zenghai; Qi, Yaru; Ed-dra, Abdelaziz; Yue, Min (Frontiers in Cellular and Infection Microbiology, 2020)
The emergence of antimicrobial-resistant (AR) Salmonella has a major concern worldwide. This study was designed to determine the AR profiles and serovars distribution of Salmonella enterica isolated from different breeds of breeder chickens in the province of Henan, China. For this, 2,139 dead embryo samples were collected from 28 breeder chicken hatcheries, representing two domestic and four foreign breeds. The samples were subjected to the isolation and identification of Salmonella by PCR. The confirmed strains were serotyped according to the Kauffmann-White scheme and their AR profiles against 20 antimicrobial agents were determined by Kirby-Bauer (K-B) disc diffusion method. The results of this study showed the prevalence of Salmonella in 504 strains (23.56%) with a high abundance in southern regions of Yellow River (28.66%, n = 495, N = 1,727) compared to the northern regions (2.18%, n = 9, N = 412) (p < 0.0001). The domestic breeds were more contaminated than imported breeds (p < 0.0001). However, the contamination rate of samples recovered from M-hatcheries was the highest (p < 0.0001). Serotyping method identified 12 serovars, with the dominance of S. Pullorum (75.79%), followed by S. Enteritidis (7.14%). The AR assay showed high resistant to ciprofloxacin (77.00%), sulfisoxazole (73.00%), and ampicillin (55.60%), as well as 98.81% (n = 498) of the isolated strains, were resistant to at least one antimicrobial and 69.64% (n = 351) were resistant to three or more antimicrobials. Among them, one strain of S. Thompson was resistant to 15 antimicrobial agents belonging to eight different classes. In conclusion, Salmonella strains isolated in this study were multidrug-resistant (MDR), presenting a serious problem for human and animal health. Therefore, it is necessary to monitor, control, and rationalize the use of antimicrobials agents in chicken farms in order to limit the increasing resistance against the recent antimicrobial agents.